INDICATORS OF EARLINESS, FIBER YIELD, FIBER INDEX, AND QUALITY TRAITS IN THE VARIETIES INVOLVING BOLLGARD GENE SAMPLES (Eureka Journal of Agricultural Science & Bio-Innovation, 2026)
In the studies, from the 22 lines of the (C-6524 × VT) combination involving the BT gene sample, lines with earliness up to 115.0 days, fiber yield above 39.0%, and fiber index over 9.0 g, were selected based on analyses of fiber quality, bollworm resistance, and wilt disease tolerance, with the aim of developing new lines and varieties combining these valuable agronomic traits.
Keywords: Cotton, hybrid, simple hybrid, lines, varieties, Bt gene genotype, variability, earliness, fiber index, lint yield.